(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2020)
This article has no abstract. The first 100 words appear below: A 12-year-old girl, 2nd issue of non-consanguineous parents, immunized as per EPI schedule, presented with the history of hematemesis and melena 3 months back and abdominal distension for 1 year. After the episodes of hematemesis and melena, she received 1 unit of blood transfusion. She had no history of fever, jaundice, abdominal trauma, umbilical catheterization, umbilical sepsis, severe dehydration, offending drug intake and abdominal trauma or any surgery.